City Information Models (CIMs) as precursors for Urban Digital Twins (UDTs): A case study of Lancaster - Cureton, Paul; Hartley, Elliot (Frontiers in Built Environment, 2023)
City Information Models (CIMs) present several research challenges and are arguably pre-cursors for a roadmap to the transition to Urban or City Digital Twins (UDTs/CDTs) and broader smart city drives. In a period of digital transformation in urban planning, CIMs are primarily designed to intersect and merge urban GIS/BIM in what is termed GeoBIM. CIMs are often cloud-based geospatial services and data repositories with one-way data connections, which differ from integrated and high-fidelity cyber-physical complex systems for digital twins (DTs). However, there is a lack of precision in terms of defining CIMs and UDTs, and this paper examines four broad sociotechnical research challenges regarding the progress of CIMs toward full UDTs/CDTs, including (1) technical training for adoption, (2) acquisition strategies for aerial data and remote sensing, (3) data licensing types and system management, and (4) stakeholder engagement with CIM platforms. These four research challenges and digital transformation are discussed by using back-casting futuring methods, establishing a framework for CIMs through co-designed workshops, and explored in the Lancaster City Information Model (LCIM) prototype. The LCIM, as a resulting case study, was developed for architects, planners, and stakeholders to engage with 3D urban models and urban analytics (view sheds, masterplan scenarios, and solar potentials of buildings) from 2019 to 2021 to address digital inequality in planning and data fragmentation. The framework and prototype results resulted in the most extensive 3D open urban dataset published in the UK, consisting of a baseline of 1″+/− buildings and infrastructure and 7.5 cm aerial imagery and a framework for developing transitions from CIMs to UDTs. The delivery of this case and the resulting published dataset highlights the essential research needed regarding definitions and precision around terminology and systems between CIMs and UDTs and four applied challenges in digital transformation and future socio-technical relationships.